A Time series analysis of residential energy demand forecast in Nigeria - OKACHI, SIMEON; Akpama, E.J; Ogar, V. N (IJRDO - Journal of Electrical And Electronics Engineering, 2019)
The supply of efficent, reliable and affordable power is a major criteria to enhance development in any given country. Up till now Nigeria has battling with low economic growth and decay of infrastructure largely due to power outages and low generation as well as transmission. The development of energy infrastrucure is capital intensive which must be carefully and holistically planned especially when furture expansion fram work is taken into consideration. This researched paper is aimed at carefully forecasting the quantity of power that will efficiently supply the residential areas in nigeria for meaninful economic growth as well as industrialization. Using Time Series Analysis as tool for forecasting,The outcome shows that the country need to improve on her generation , transmission and distribution facilities to deliver  atleast 20,000MW on or before 2030 .